The end of leadership - Kellerman, Barbara (New York : Harper Business, 2012)
"One of our foremost leadership experts dismantles obsolete assumptions and stimulates a new conversation about leadership in the twenty-first century. Becoming a leader has become a mantra. The explosive growth of the 'leadership industry' is based on the belief that leading is a path to power and money, a medium for achievement, and a mechanism for creating change. But there are other, parallel truths: that leaders of every stripe are in disrepute; that the tireless and often superficial teaching of leadership has brought us no closer to nirvana; and that followers nearly everywhere have become, on the one hand, disappointed and disillusioned, and, on the other, entitled and emboldened. The End of Leadership tells two tales. The first is about change--about how and why leadership and followership have changed over time, especially in the last forty years. As a result of cultural evolution and technological revolution, the balance of power between leaders and followers has shifted--with leaders becoming weaker and followers stronger. The second narrative is about the leadership industry itself. In this provocative and critical volume, Barbara Kellerman raises questions about leadership as both a scholarly pursuit and a set of practical skills: Does the industry do what it claims to do--grow leaders? Does the research justify the undertaking? Do we adequately measure the results of our efforts? Are leaders as all-important as we think they are? What about followers? Isn't teaching good followership as important now as teaching good leadership? Finally, Kellerman asks: Given the precipitous decline of leaders in the estimation of their followers, are there alternatives to the existing models--ways of teaching leadership that take into account the vicissitudes of the twenty-first century? The End of Leadership takes on all these questions and then some--making it necessary reading for business, political, and community leaders alike."--Publisher's website.
Introduction: twenty-first century leadership -- and followership -- Power shift -- Historical trajectory--lessening power -- Cultural constraints--leveling the playing field -- Technological imperatives--losing control -- Shifting sands -- Social contract--undermining the understanding -- American experience--downgrading leaders -- Worldwide momentum--upgrading followers -- Paradigm shift -- Leadership industry--leading as mantra -- Leadership complete--leading in time.
Includes bibliographical references and index.
Keywords: Leadership